The Patterns and Associations between Attitudes towards Active Travel and Physical Activity among Residents in Three Selected Provinces of Thailand - Topothai, Thitikorn; Topothai, Chompoonut; Suphanchaimat, Rapeepong (Outbreak, Surveillance, Investigation & Response (OSIR) Journal, 2024)
Active travel offers opportunities for regular physical activity, influenced by socio-demographic, socio-economic, and socio-psychological determinants. This study investigated the associations between positive attitudes towards active travel environments and literacy with sufficient physical activity in Thailand. A cross-sectional study was conducted with 343 residents recruited from three communities in 2019. A self-administered questionnaire collected data on demographics, physical activity levels (using the Global Physical Activity Questionnaire), and attitudes towards 11 supportive conditions for active travel. Factor analysis identified three factors: (1) attitudes towards public transport environments, capturing perceptions of convenience, attractiveness, and affordability; (2) attitudes towards walking and cycling environments, reflecting supportive conditions like safety and conduciveness; and (3) active travel literacy, relating to awareness and understanding of active travel concepts. Multivariable logistic regression analysis revealed that participants with positive attitudes towards public transport environments (adjusted odds ratio (AOR) 2.06, 95% confidence interval (CI) 1.01–4.17) and active travel literacy (AOR 2.93, 95% CI 1.10–7.79) had a significantly higher likelihood of achieving sufficient physical activity. Policymakers should prioritize enhancing the convenience, attractiveness, and affordability of public transport and promote educational campaigns to boost active travel literacy and encourage active travel behaviors.